Effect of metoprolol in patients with renal hypertension - Yasumoto, R (Hinyokika kiyo. Acta urologica Japonica, 1988)
Eighteen patients with renal hypertension were treated with metoprolol (Seloken) for more than 3 months. Compared with the pretreatment value, the mean blood pressure decreased by 6.0, 11.2, 9.2 and 12.2 mmHg, after 2 weeks and 3, 6 and 12 months of treatment with metoprolol, respectively. All the differences observed were statistically significant (p less than 0.01). The blood pressure lowering effect of metoprolol was observed in 12 of the 17 patients (70.6%) examined. Decrease in plasma renin activity was seen in most of the responders. Although the number of patients was limited, the plasma level of metoprolol was also measured. The results indicated no sign of accumulation of metoprolol in the body. Moderate deterioration in renal function was observed in 1 patient but the treatment with metoprolol could be continued. Metoprolol administration had to be discontinued in 1 patient, who developed asthma. There were no other serious side effects